Study protocol and implementation details for a pragmatic, stepped-wedge cluster randomised trial of a digital adherence technology to facilitate tuberculosis treatment completion. Issue 11 (27th November 2020) - Crowder, Rebecca; Kityamuwesi, Alex; Kiwanuka, Noah; Lamunu, Maureen; Namale, Catherine; Tinka, Lynn Kunihira; Nakate, Agnes Sanyu; Ggita, Joseph; Turimumahoro, Patricia; Babirye, Diana; Oyuku, Denis; Berger, Christopher Allen; et al.
Abstract : Introduction: Low-cost digital adherence technologies (DATs) such as 99DOTS have emerged as an alternative to directly observed therapy (DOT), the current standard for tuberculosis (TB) treatment supervision. However, there are limited data to support DAT scale-up. The 'DOT to DAT' trial aims to evaluate the effectiveness and implementation of a 99DOTS-based TB treatment supervision strategy. Methods and analysis: This is a pragmatic, stepped-wedge cluster randomised trial, with hybrid type 2 effectiveness-implementation design. The trial will include all adults (estimated N=1890) treated for drug-susceptible pulmonary TB over an 8-month period at 18 TB treatment units in Uganda. Three sites per month will switch from routine care (DOT) to the intervention (99DOTS-based treatment supervision) beginning in month 2, with the order determined randomly. 99DOTS enables patients to be monitored while self-administering TB medicines. Patients receive daily automated short message service (SMS) dosing reminders and confirm dosing by calling toll-free numbers. The primary effectiveness outcome is the proportion of patients completing TB treatment. With 18 clusters randomised into six steps and an average cluster size of 15 patients per month, the study will have 89% power to detect a 10% or greater increase in treatment completion between the routine care and intervention periods. Secondary outcomes include more proximal effectiveness measures as well as quantitative and qualitative assessments of the reach, adoption and implementation of the intervention. Ethics and dissemination: Ethics approval was granted by institutional review boards at Makerere University School of Public Health and the University of California San Francisco. Findings will be disseminated through peer-reviewed publications, presentations at scientific conferences and presentations to key stakeholders. Trial registration number: PACTR201808609844917.